”FOR CROP PROTECTION” Establishment medallion in honour of Antal Gulyás (1884-1980) - Kövics, György (Acta Agraria Debreceniensis, 2011)
The Public Utility for Development of Crop Protection Teaching (NOFKA) and The Hajdú-Bihar County Regional Association of Hungarian Chamber of Crop Protection Specialists and Plant Doctors (Chamber) established a joined Award Committee in September of 2011, which intend to serve as moral appreciation to prominent persons with excellent achievements by award Antal Gulyás medallion for crop protection“ which are available for outstanding teachers, researchers, and practical plant protectionists. The members of Committee: dr. István Szarukán, president, dr. György Kövics, secretary, dr. István Dávid member (Public Utility), dr. László Kiss, president, dr. Gábor Tarcali, secretary (Chamber). Handing over of medallion, charter and gold badge will be happened generally once a year in a special ceremony. The award was established in commemoration of Antal Gulyás, who was the first eminent professor of plant protection in Debrecen and reached outstanding achievements in the field of teaching of agronomists for more than 30 years, and research on plant pathology. He became one of the first Honoris Causa Doctors of Debrecen Agricultural University in 1978. The Committee made its decision on the first meeting that the first medallion will be award to dr. Oszkár Tóth retired reader of plant pathology for his excellence in teaching plant protection in 2011. His laudation is available in a separate article of this issue.